2019
DOI: 10.3389/fnbeh.2019.00049
|View full text |Cite
|
Sign up to set email alerts
|

Beta Modulation Depth Is Not Linked to Movement Features

Abstract: Beta power over the sensorimotor areas starts decreasing just before movement execution (event-related desynchronization, ERD) and increases post-movement (event-related synchronization, ERS). In this study, we determined whether the magnitude of beta ERD, ERS and modulation depth are linked to movement characteristics, such as movement length and velocity. Brain activity was recorded with a 256-channels EEG system in 35 healthy subjects performing fast, uncorrected reaching movements to targets located at thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 37 publications
3
32
0
Order By: Relevance
“…Similarly, no direct relationship between movement parameters and ERS, despite an ERS difference between extension-flexion and flexion-extension movements, had been found [66]. Also, a recent work from our research group indicated that no link between movement extent and beta modulation magnitude is detected in upper limb reaching movements [67]. Indeed, movement-related beta oscillations may be related to sensorimotor integration processes associated with movement planning and execution rather than explicitly reflecting the coding of distinct movement features [68, 69].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, no direct relationship between movement parameters and ERS, despite an ERS difference between extension-flexion and flexion-extension movements, had been found [66]. Also, a recent work from our research group indicated that no link between movement extent and beta modulation magnitude is detected in upper limb reaching movements [67]. Indeed, movement-related beta oscillations may be related to sensorimotor integration processes associated with movement planning and execution rather than explicitly reflecting the coding of distinct movement features [68, 69].…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of this test have been detailed in a recent paper (Tatti et al, 2019) and are illustrated in Figure 1B.…”
Section: Mov Testmentioning
confidence: 99%
“…In particular, recent studies from our laboratory have shown that extended practice in a reaching task is associated with a significant increase of the beta ERD-ERS peak-to-peak amplitude (i.e., beta modulation depth) over parietal and frontal regions. This measure is independent from mean power changes and is mostly due to amplitude increases of the peak ERS (Moisello et al, 2015;Nelson et al, 2017;Ricci et al, 2019a;Tatti et al, 2019). Interestingly, the beta modulation increase during the task is followed by a local beta power increase during the resting EEG (Moisello et al, 2015) and returns to baseline values when tested 24 h later (Nelson et al, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…We aim to study whether pre-and post-stimulus imaginary coherence of within and/or across sensorimotor connectivity of calibration data can predict future feedback (online) performance in a group of 80 participants. Besides, and taking into account that the dynamics of the data are individual (Ricci et al, 2019;Tatti et al, 2019), we systematically control for the influence that SNR of the oscillatory signals might have on the extracted connectivity estimates.…”
Section: Introductionmentioning
confidence: 99%